"We've Cared for the Dead since We Started Caring": COVID‐19 and Our Relationship to Public and Private Deathcare. (26th May 2020) - Zavattaro, Staci M.
Abstract: The COVID‐19 pandemic has highlighted public organizations' challenges related to deathcare. Within the emergency management literature, and specifically within public administration, there is a gap when it comes to planning past death. Using data from interviews with 35 municipal cemetery managers throughout the United States, I show how our unwillingness to talk about or plan for death, coupled with cemetery managers who are underfunded and often left out of emergency management planning processes, needs increased attention. While many deathcare best practices were deployed to respond to the virus, cemetery managers often are not part of the planning process.